2013
DOI: 10.1534/genetics.113.151571
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Methods for Analyzing Drosophila Germline Mutation Rates

Abstract: Most studies of mutation rates implicitly assume that they remain constant throughout development of the germline. However, researchers recently used a novel statistical framework to reveal that mutation rates differ dramatically during sperm development in Drosophila melanogaster. Here a general framework is described for the inference of germline mutation patterns, generated from either mutation screening experiments or DNA sequence polymorphism data, that enables analysis of more than two mutations per fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Using the same notation as Fu (2013), the information conveyed by mutation(s) in a family can be represented by a mutation patternκ=i,j,kin which each element represents a mutation and its value is the number of offspring carrying the mutation, or simply the size of the mutation . After a line obtains a mutation of lethality ≥ d %, a further mutation will likely do nothing or increase the level of lethality, but the effect is usually difficult to distinguish from the first one under our experimental setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same notation as Fu (2013), the information conveyed by mutation(s) in a family can be represented by a mutation patternκ=i,j,kin which each element represents a mutation and its value is the number of offspring carrying the mutation, or simply the size of the mutation . After a line obtains a mutation of lethality ≥ d %, a further mutation will likely do nothing or increase the level of lethality, but the effect is usually difficult to distinguish from the first one under our experimental setting.…”
Section: Methodsmentioning
confidence: 99%
“…The estimate of μ = ( u 1 , … u I ) and statistical tests about them were performed through the maximum likelihood approach developed in Gao et al (2011) and further refined in Fu (2013). The inference makes use of the information about population dynamics, intervals of cell divisions, and coalescent structure of the sample genealogy (Figure 1), but in essence, the inference framework is based on evaluating the likelihood function
Figure 1Population dynamics and an example of the genealogy of four sperm sampled at the time at which maximal 38th cell division has occurred (adapted from Fu 2013).
L=fκpf(κ)nf(κ)where f represents family size, κ is a mutation pattern for a given family size f , n f ( κ ) is the number of occurrences of pattern κ in families of size f , and p f ( κ ) is the probability of mutation pattern κ , which is a function of μ and coefficients that are derived from the dynamics of the germline population.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study [ 1 3 ] on the recessive lethal or nearly lethal mutations during the germline development of male Drosophila melanogaster shed some light on this important area of biology. The experimental data reported in Gao et al [ 1 , 3 ] and Fu [ 2 ] were obtained from a large scale mutation accumulation and screening experiment, the basis for which has been refined over the years [ 4 – 6 ]. In general, the germline development of a male Drosophila melanogaster consists of about 36–40 cell divisions, among which the first 14 cell divisions belong to the cleavage stage, the last 5 to spermatogenesis, and those in between to gastrulation and organogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the germline development of a male Drosophila melanogaster consists of about 36–40 cell divisions, among which the first 14 cell divisions belong to the cleavage stage, the last 5 to spermatogenesis, and those in between to gastrulation and organogenesis. Gao et al [ 1 , 3 ] and Fu [ 2 ] concluded that the mutation rates in the mature young male Drosophila melanogaster vary significantly during the germline development. In particular, mutation rate for the first cell division is the highest, followed by those during spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation